Reforming Social Welfare in Germany: An Applied General Equilibrium Analysis - Reinhold Schnabel; Nicole Gürtzgen; Stefan Boeters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper analyses the effects of a social assistance reform in Germany. In contrast to studies which are based on microsimulation methods we use a computable general equilibrium model which incorporates a discrete choice model of labour supply to simulate a variety of reform scenarios. The main contribution is that we are able to identify general equilibrium effects of a reform on wages and unemployment. The simulation results show that general equilibrium wage reactions tend to mitigate labour supply effects. Moreover, the simulations indicate that substantial employment effects are to be expected only from major cuts in welfare payments.
Keywords: J22; D58; J51; 330; social assistance; discrete labour supply model; applied general equilibrium; Sozialhilfe; Sozialreform; Arbeitsangebot; Diskrete Entscheidung; Niedriglohn; Beschäftigungseffekt; Arbeitslosigkeit; Öffentlicher Transfer; Allgemeines Gleichgewicht; CGE-Modelling; Wirtschaftspolitische Wirkungsanalyse; Deutschland